Getting it right: youth employment policy within the EU - Pastore, Francesco (Bonn, 2017)
"This essay discusses the determinants of youth unemployment within the EU and then the alternative policy options currently at stake. We argue that youth unemployment regards especially some peripheral EU countries and is due to a mix of factors that should be addressed more vigorously, starting from expansionary fiscal and monetary policy. The guiding line should be to reform the Maastricht Treaty so as to allow each EU country to reach the Europe 2020 targets. Moreover, especially in the peripheral countries drastic reforms of the school-to-work transition regimes are needed, including not only the European Youth Guarantee, which is underfinanced, but also the introduction of better links between the education system and the labor market. The past emphasis on labor market reforms, instead, should be reconsidered."